High strain rate deformation behaviour analysis of recycled aluminium alloys AA6061 reinforced alumina oxide Al2O3 using Taylor cylinder impact test / N. Ma’at, C. S. Ho and M. K. Mohd Nor - Ma’at, N.; Ho, C. S.; Mohd Nor, M. K. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
The deformation behaviour and fracture mechanism of reinforced recycled aluminium alloy are still an open and exciting area to be explored. Based on this motivation, this paper investigates the deformation behaviour, and fracture mode of recycled aluminium alloy AA6061 reinforced alumina oxide at a high strain rate using the Taylor cylinder impact test. The deformation behaviour analysis was also compared with the behaviour shown by the recycled AA6061 without reinforcement material. The geometric profile of the deformed specimen was used to analyse the deformation behaviour and fracture mode, including the relation with the impact deformation characteristics. Three different fracture modes were observed within the impact velocity of 190-370 m/s. The reinforced recycled AA6061 showed a better strength performance with higher critical impact velocity than the unreinforced recycled AA6061. The damage deformation behaviour was studied using Scanning Electron Microscope (SEM). The results showed that the damage agents were initiated, grew, and coalesced during mild ductility deformation. Damage progression was finally examined using ImageJ software and characterized average voids size. The decrement of voids size was quite significant under tensile splitting and petalling fracture modes compared to the mushrooming due to severe localized plastic strain deformation around this plastic deformation zone. Therefore, the increasing impact velocity increases the severity of damage progression of the reinforced recycled AA6061.